Metocean: Sustainable Consideration and Situation Report on Post Production Sharing Contract (PSC) of Petronas Carigali - Shahir Liew, Mohd (2010)
Petronas is currently one of the “oil majors” in the world. Established in 1974 through The Petroleum Development Act, Petronas is now listed in the Fortune 100 and considered as one of the top employer of choice [1]. Petronas holds exclusive ownership and control over all petroleum resources in Malaysia and regulates E & P activities through Production Sharing Contract (PSC). There are 62 PSCs awarded to oil and gas companies. Historically and in the then Malaya, the Anglo-Saxon, currently known as Shell Oil Company was given the sole right to explore petroleum resources in Sarawak and the first oil was struck in Miri Field on the 22 December, 1910. Since then, Petronas Carigali Sdn Bhd (PCSB) was incorporated in 1978 as an exploration and production arm of PETRONAS. PCSB first developed the Duyung Gas Field in 1980 and Dulang Oil Field in 1991. At this juncture, the oil companies operating in Peninsular Malaysia and East Malaysia such as Esso, Shell, Conoco, and Mobil were given a concession to explore and develop the oil fields. Today, Petronas has international presence to explore other oil fields as well. Currently, there are many concessions which will be expiring soon. Upon expiry of these concessions, PCSB will be tasked as the custodian of these platforms. In view of this, PCSB is taking the pro-active step now in developing short to long term strategies related to the performance of the platforms under several scenarios, in particular, the reliability of the platforms to serve out the remaining lifespan which the platforms have been designed for initially at the time of commissioning subject to the environmental loads at the existing location of the platforms. This is particularly applicable to the offshore platforms. As an advocate of sustainable design and growth in the energy business, PCSB remains committed to ensure that the offshore platforms remain resilient and reliable on its own accord as designed originally or through a series of structural modifications to the platforms in ensuring that the platforms can continue to operate under adverse environmental loads with acceptable level of risk and without affecting the marine environment which the platform is located. This sustainable review on the design of the offshore platforms commences with the environmental loads which may affect the performance of the platforms. These environmental loads are derived from the winds, waves, and currents.